Cover Image, Volume 137, Issue 43. Issue 43 (12th August 2020) - Modak, Piyush; Hammond, Willis; Jaffe, Michael; Nadig, Malavika; Russo, Richard
Abstract : This figure by Piyush Modak and colleagues shows a patented porous architecture (20 x magnification) formed by a dynamic Schiff base network between acrylated chitosan (aCHN) & oxidized dextran (oDEX). This aCHN‐oDEX network is a tunable, platform technology with various medical applications. Schiff base bonds in this network are mobile and reversible allowing additional Schiff base bonds to form over time, leading to a lower energy state and densification. In addition, the network shrinks, even when completely immersed in physiological solution, instead of swelling. And the shrinkage allows the 3D network to be used in enclosed structures such as the brain and spine. DOI: 10.1002/app.49756